Convergence of Nuclear Magnetic Shieldings in the Kohn-Sham Limit for Several Small Molecules - Kupka, Teobald; Stachów, Michał; Nieradka, Marzena; Kaminsky, Jakub; Pluta, Tadeusz (Journal of chemical theory and computation, 2010)
Convergence patterns and limiting values of isotropic nuclear magnetic shieldings were studied for several small molecules (N2, CO, CO2, NH3, CH4, C2H2, C2H4, C2H6, and C6H6) in the Kohn-Sham limit. Individual results of calculations using dedicated families of Jensen's basis sets (pcS-n and pcJ-n) were fitted toward the complete basis set limit (CBS) using a simple two-parameter formula. Several density functionals were used; calculated vibrational corrections (ZPV) applied; and, for comparison purposes, similar calculations performed using RHF, MP2, SOPPA, SOPPA(CCSD), and CCSD(T) methods and additionally, the aug-cc-pVTZ-J basis set. Finally, the CBS estimated results were critically compared with earlier reported literature data and experimental results. Among 42 studied DFT methods, the KTn and "pure" functionals produced the most accurate heavy atom isotropic nuclear shieldings.